The contributions of universities in spreading a culture of social peace amongst youth - Study applied to Umm Al-Qura University - Saudi Arabia – - Khalifa, Heba Ahmed Abdel-Latif; Al-Zahrani, Nasser Awad Saleh (Journal of Humanities & Social Sciences, 2020)
The study sought to identify the universities' contributions to spreading the culture of social peace among Saudi youth. This is done by identifying its contributions to spreading (values ​​of tolerance, values ​​of justice, values ​​of freedom) among young people. And identify the obstacles that universities face in spreading a culture of social peace among young people This study relied on the descriptive analytical method. The researcher used the questionnaire tool that was applied to 137 workers at Umm Al-Qura University and 64 students at the university. The data will also be coded and statistically analyzed via SPSS. V. 21. 0 programs. The study concluded that the universities' contributions to spreading the values ​​of tolerance among young people to promote a culture of social peace are considered to be of the medium type, as the total weighted frequency (1351) and the relative degree of dimension (0. 65). The university’s contributions to spreading the values ​​of justice among young people to foster a culture of social peace are of a weak type, with a total weighted frequency (1321) and a relative degree of dimension (0. 64). Universities' contributions to spreading the values ​​of freedom among young people to foster a culture of social peace are considered to be of medium type, with a weighted total of duplicates (1341) and a weighted weight (0. 65). The study also came up with a proposed vision to activate the contributions of universities in spreading a culture of social peace among Saudi youth in accordance with the vision of 2030
Keywords: contributions; universities; culture of social peace; youth